Target Organ Specific Activity of Drosophila MRP (ABCC1) Moderates Developmental Toxicity of Methylmercury. - Prince, L.; Korbas, M.; Davidson, P.; Broberg, K.; Rand, M.D. (Toxicological Sciences, 2014)
Methylmercury (MeHg) is a ubiquitous and persistent neurotoxin that poses a risk to human health. Although the mechanisms of MeHg toxicity are not fully understood, factors that contribute to susceptibility are even less well known. Studies of human gene polymorphisms have identified a potential role for the multidrug resistance-like protein (MRP/ABCC) family, ATP-dependent transporters, in MeHg susceptibility. MRP transporters have been shown to be important for MeHg excretion in adult mouse models, but their role in moderating MeHg toxicity during development has not been explored. We therefore investigated effects of manipulating expression levels of MRP using a Drosophila development assay. Drosophila MRP (dMRP) is homologous to human MRP1-4 (ABCC1-4), sharing 50% identity and 67% similarity with MRP1. A greater susceptibility to MeHg is seen in dMRP mutant flies, demonstrated by reduced rates of eclosion on MeHg-containing food. Furthermore, targeted knockdown of dMRP expression using GAL4>UAS RNAi methods demonstrates a tissue-specific function for dMRP in gut, Malpighian tubules, and the nervous system in moderating developmental susceptibility to MeHg. Using X-ray synchrotron fluorescence imaging, these same tissues were also identified as the highest Hg-accumulating tissues in fly larvae. Moreover, higher levels of Hg are seen in dMRP mutant larvae compared with a control strain fed an equivalent dose of MeHg. In sum, these data demonstrate that dMRP expression, both globally and within Hg-targeted organs, has a profound effect on susceptibility to MeHg in developing flies. Our findings point to a potentially novel and specific role for dMRP in neurons in the protection against MeHg. Finally, this experimental system provides a tractable model to evaluate human polymorphic variants of MRP and other gene variants relevant to genetic studies of mercury-exposed populations.